Estudio de factibilidad para la creación de una empresa productora y comercializadora de fundas biodegradable en la Isla Santa Cruz provincia de Galápagos - Coque Arellano, Maria Rosa (2024)
This feasibility study for the creation of a company producing and marketing biodegradable bags on Santa Cruz Island in the Galápagos province, specifically in the Puerto Ayora parish, seeks to determine the feasibility of an investment project focused on ecological solutions. The biodegradable bags are designed to replace traditional plastics and contribute to the conservation of the island's natural environment, a UNESCO World Heritage site. A project-based methodological design was conducted, which included a descriptive field study and a mixed approach. Data was obtained through surveys applied to a probabilistic sample of 107 commercial establishments and an interview with the CEO of the company Marea Alta........